2017
DOI: 10.1021/acs.est.7b00294
|View full text |Cite
|
Sign up to set email alerts
|

Response of Soil Microbial Communities to Elevated Antimony and Arsenic Contamination Indicates the Relationship between the Innate Microbiota and Contaminant Fractions

Abstract: Mining of sulfide ore deposits containing metalloids, such as antimony and arsenic, has introduced serious soil contamination around the world, posing severe threats to food safety and human health. Hence, it is important to understand the behavior and composition of the microbial communities that control the mobilization or sequestration of these metal(loid)s. Here, we selected two sites in Southwest China with different levels of Sb and As contamination to study interactions among various Sb and As fractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(39 citation statements)
references
References 67 publications
1
35
1
Order By: Relevance
“…The size of each node is proportional to the number of connections (degree). Bigger nodes indicate stronger and more significant correlations with other nodes and, therefore, may be important members in the community (Sun et al ., ). The most densely connected node in each module is defined as a ‘hub’.…”
Section: Resultsmentioning
confidence: 97%
“…The size of each node is proportional to the number of connections (degree). Bigger nodes indicate stronger and more significant correlations with other nodes and, therefore, may be important members in the community (Sun et al ., ). The most densely connected node in each module is defined as a ‘hub’.…”
Section: Resultsmentioning
confidence: 97%
“…Arthrobacter was positively correlated with Sb tot (p < 0.05), Sb avail (p < 0.05) and Pb avail (p < 0.05), while it was negatively correlated with As pbioavail as well as Hg pavail , which identified Arthrobacter as a core microorganism in the soils contaminated by Sb and As (Sun et al 2017). It was previously isolated from Pb-contaminated and Cd-contaminated soil and was not dependent on the concentration of metals in soils (Kozdrój and van Elsas 2001).…”
Section: Relationship Between Toxic Element Contamination and Bacterimentioning
confidence: 92%
“…Recently, using Illumina sequencing of 16S rRNA, studies reported the investigation of the correlation between microbial community profiles and concentrations of Sb and As in soils and water (Sun et al 2016a, b;Xiao et al 2016Xiao et al , 2017. Recent work also includes the use of metagenomics and metagenomic binning to investigate the soil microflora response to As and Sb contamination, providing progresses using state-ofthe-art molecular tools to unravel the interactions between microbiota and Sb and As (Sun et al 2018;Sun et al 2017). Significant positive correlation was demonstrated between groups and the extractable fractions of Sb and As in soils (Sun et al 2016a, b;Xiao et al 2016Xiao et al , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Water bacterial and fungal community sequence reads were first filtered by the QIIME pipeline [ 22 ]. The quality-trimmer removed reads are shorter than 50 bp [ 23 ]. After quality filtering and chimera removal, the abundance-based coverage estimator (ACE) index, Chao richness estimator ( Chao 1), Shannon diversity ( H ') and Simpson diversity (1/ D ) indices were calculated by the MOTHUR package (version 1.22.2 ) using Operational Taxonomic Units (OTUs) grouped at 0.97 level [ 24 ].…”
Section: Methodsmentioning
confidence: 99%